2018
DOI: 10.14715/cmb/2018.64.5.8
|View full text |Cite
|
Sign up to set email alerts
|

Intradiscal ozone therapy for lumbar disc herniation

Abstract: The rationale behind intradiscal O 2 -O 3 therapy is the pain elicited by the mechanical compression of the nerve root, which is associated with periganglionic and periradicular inflammation. This study aimed to determine the effect of intradiscal ozone injection on pain score and satisfaction of patients with low back pain (LBP) secondary to disc herniation. Patients with LBP diagnosed with disc herniation were enrolled in this clinical trial. After prepping and draping the area, intradiscal injection of ozon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 15 publications
0
15
0
4
Order By: Relevance
“…To date, O 3 therapy has been widely used in oncology, gynecology, skin and mucosal infections, pain management, and other medical conditions because of its anti-inflammatory, antioxidant, antiseptic, and disinfectant properties [26, 27]. Furthermore, O 3 treatment has been shown to have therapeutic effects in patients with lumbar disc herniation [25, 28]; Giurazza et al found that O 3 therapy used for the treatment of low back pain was safe and effective and that the benefits lasted for up to 10 years after treatment [29]. Melchionda et al reported that paravertebral injections with oxygen-ozone could induce a direct improvement in radicular inflammation and pain [10].…”
Section: Discussionmentioning
confidence: 99%
“…To date, O 3 therapy has been widely used in oncology, gynecology, skin and mucosal infections, pain management, and other medical conditions because of its anti-inflammatory, antioxidant, antiseptic, and disinfectant properties [26, 27]. Furthermore, O 3 treatment has been shown to have therapeutic effects in patients with lumbar disc herniation [25, 28]; Giurazza et al found that O 3 therapy used for the treatment of low back pain was safe and effective and that the benefits lasted for up to 10 years after treatment [29]. Melchionda et al reported that paravertebral injections with oxygen-ozone could induce a direct improvement in radicular inflammation and pain [10].…”
Section: Discussionmentioning
confidence: 99%
“…This factor is an important condition to be investigated in future studies because this distinction has not been made in many studies that evaluated the effectiveness of ozone therapy. [7,[10][11][12][13][14][15] The overall rate of procedural complication of ozone administration is 0.1%. [5] Two meta-analyses have identified the safety and effectiveness of this therapy.…”
Section: Discussionmentioning
confidence: 99%
“…that O 3 therapy is effective to control LBP associated to NP Herniated and/or DDD [34,[39][40][41][42][43][44][45][46][47][48][49]. The two main route of administration used were the intramuscular injection in the paravertebral muscles of the muscles innervated for the nerves of affected segments [39][40][41] and the percutaneous Intra disc injection [42][43][44][45][46][47][48][49]. Both administration route showed effi ciency to control the LBP in around 60 to 80% of treated patients with a diminishing of 60 to 75% in the VAS index.…”
Section: Several Clinical Reports and Clinical Trials Have Provedmentioning
confidence: 99%
“…The major cause of medical failure was and advanced degree of lumbar-sacrum osteo arthrosis related to a continuous and severe pain that lasted more than one year. Because these morphologic and clinical limitations were described by the fi rst reported treated patients [39][40][41][42][43], these 2 conditions were exclusions in the subsequent series of clinical trials [44][45][46][47][48][49].…”
Section: Several Clinical Reports and Clinical Trials Have Provedmentioning
confidence: 99%
See 1 more Smart Citation